The Local Authority Infrastructure Provision Practice in Malaysia: The Role of Private Developers - Salleh, Dani; Okinono, Otega (International Review of Management and Marketing, 2016)
Local authorities are turning to the private sectors to achieve their objective of providing local infrastructures for effective management of the local areas. Private sector and local authority have good understanding of the fundamental concept of local infrastructure provision. Despite this understanding, there are still considerable lapses of what best practice and method to adopt in the provision of local infrastructure. This study therefore examined the role of private developers in local infrastructure and the practices used by local authorities for infrastructural procurement in Malaysia. 22 local authorities and 16 developers were selected through purposive sampling method, and data collected using questionnaires was analysed using the descriptive analysis technique. The findings revealed that joint venture and complete public delivery systems; negotiations are the most commonly adopted practices and successful method applied by the local authority to securing infrastructure. One major weakness expressed by majority of the developers is difficulty to promote private sector involvement in local infrastructure development due to unregulated-procedure. This study therefore recommends that local authorities should not only be concerned on collaborative and joint approach but also in developing a well-coordinated structure and system of operations. Keywords: Local authority, Infrastructure provision, Practice. JEL Classifications: H75, H7